Երկիրը սիրում են մարդկանցով - Յուրայի Նուրիջանյան, Օլյա (Musical Armenia, 2011)
The article of PhD candidate, Yerevan State Conervatory after Komitas pedagogue Olga Y. Nurijanyan "The country is loved by the people" is about characteristic features of the public figure, popular and loved by people Adam G.Khudoyan. This is a friend's portrait that is created by the statement of facts, set forth in the writings of his contemporaries.